Oligomeric state of hypoxanthine-guanine phosphoribosyltransferase from Mycobacterium tuberculosis - Eng, Wai Soon; Keough, Dianne T; Hockova, Dana; Winzor, Donald J; Guddat, Luke W (Biochimie, 2017)
Sedimentation equilibrium and size-exclusion chromatography experiments on Mycobacterium tuberculosis hypoxanthine-guanine phosphoribosyltransferase (MtHGPRT) have established the existence of this enzyme as a reversibly associating mixture of dimeric and tetrameric species in 0.1 M Tris-HCl-0.012 M MgCl2, pH 7.4. Displacement of the equilibrium position towards the larger oligomer by phosphate signifies the probable existence of MtHGPRT as a tetramer in the biological environment. These data thus add credibility to the relevance of considering enzyme function in the light of a published tetrameric structure deduced from X-ray crystallography. Failure of 5-phospho-α-d-ribosyl-1-pyrophosphate (PRib-PP) to perturb the dimer-tetramer equilibrium position indicates the equivalence and independence of binding for this substrate (the first to bind in an ordered sequential mechanism) to the two oligomers. By virtue of the displacement of the equilibrium position towards dimer that is affected by removing MgCl2 from the Tris-HCl buffer, it can be concluded that divalent metal ions, as well as phosphate, can affect the oligomerization. These characteristics of MtHGPRT in solution are correlated with published crystal structures of four enzyme-ligand complexes.
Keywords: chlorid hořečnatý; Hypoxanthine Phosphoribosyltransferase; Enzyme activity; Oligomers; hypoxanthinfosforibosyltransferasa; Protein Multimerization; Magnesium Chloride; Protein Conformation; Structural biology; Hypoxanthine−guanine phosphoribosyltransferase; Three-dimensional structure; Mycobacterium tuberculosis; konformace proteinů; multimerizace proteinu